2022
DOI: 10.1111/andr.13185
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of letrozole or anastrozole in the treatment of male infertility with low testosterone‐estradiol ratio: A meta‐analysis and systematic review

Abstract: Background: Aromatase inhibitors (AIs) have been used to treat male infertility for decades. However, due to the lack of large-scale randomized controlled studies and basic research, the efficacy and safety of AIs in the treatment of male infertility remain controversial. Therefore, it is necessary to conduct an evidence-based preliminary evaluation of the existing clinical trials of AIs in the treatment of male infertility. Method: A comprehensive literature search was performed in the PubMed, Embase, Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
5
0
3
Order By: Relevance
“…8 Accordingly, the recommended dose of letrozole is 2.5 mg/day for postmenopausal women with advanced breast cancer previously treated with antiestrogens. 9,10 Development of targeted drug delivery systems (DDSs) has received extensive attention. 12,13,14,15 The combination of medicine and nanotechnology has modified multifunctional nanocarriers that can be loaded with different drugs.…”
Section: Introductionmentioning
confidence: 99%
“…8 Accordingly, the recommended dose of letrozole is 2.5 mg/day for postmenopausal women with advanced breast cancer previously treated with antiestrogens. 9,10 Development of targeted drug delivery systems (DDSs) has received extensive attention. 12,13,14,15 The combination of medicine and nanotechnology has modified multifunctional nanocarriers that can be loaded with different drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The role of estradiol in spermatogenesis is still a matter of debate. A meta-analysis of 666 men who received either letrozole or anastrozole due to high estradiol levels found that after treatment, FSH, LH, testosterone, and sperm concentration improved significantly [ 26 ]. However, motility was negatively impacted by aromatase inhibitor therapy, leading the authors to recommend a one-week cessation of medical treatment prior to sperm retrieval [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 666 men who received either letrozole or anastrozole due to high estradiol levels found that after treatment, FSH, LH, testosterone, and sperm concentration improved significantly [ 26 ]. However, motility was negatively impacted by aromatase inhibitor therapy, leading the authors to recommend a one-week cessation of medical treatment prior to sperm retrieval [ 26 ]. In our study, we conducted a subset analysis comparing post-treatment semen parameters and hormone levels in men with T/E ratios of <10 versus ≥10, but we did not find any significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the negative feedback exerted by estrogen on HPT, reducing estrogen formation (ARI) or action (SERM) have been proposed to stimulate testicular function [17,35,36]. In meta-analyses, SERM were indeed able to induce on average a 7 nmol/L increase in total T by stimulating a 5 mU/L increase in Gn levels [37,38].…”
Section: Antiestrogensmentioning
confidence: 99%